2005
DOI: 10.1007/s00125-005-1895-z
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid-induced differential regulation of the genes encoding peroxisome proliferator-activated receptor-γ coactivator-1α and -1β in human skeletal muscle cells that have been differentiated in vitro

Abstract: Aims/hypothesis: The transcriptional coactivator peroxisome proliferator-activated receptor-γ coactivator-1α (PGC-1α) enhances metabolically relevant pathways, such as gluconeogenesis, fatty acid oxidation, thermogenesis, oxidative phosphorylation and mitochondrial biogenesis. Since regulation of the expression of the gene encoding PGC-1α (PPARGC1A) by nutrients/metabolites has not been assessed in detail, the aim of this study was to determine whether PPARGC1A (and PPARGC1B) expression is modulated by common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
29
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 11 publications
(17 reference statements)
1
29
0
1
Order By: Relevance
“…In the present study, gene expression of PGC1␣ was increased in response to fatty acids, but the relative response was blunted in diabetic myotubes compared with control cells. In C2C12 myotubes, PGC1␣ expression was enhanced after 4 h but reduced after 16 h of incubation with palmitic acid (35), whereas unsaturated fatty acids like oleic acid and linoleic acid enhanced PGC1␣ expression in human myotubes (36). Our data suggest that the reduced capacity for complete mitochondrial fatty acid oxidation observed for type 2 diabetes myotubes might be related to suboptimal responses in expression of PGC1␣, e.g., when the myotubes are exposed to fatty acids.…”
Section: Discussionmentioning
confidence: 73%
“…In the present study, gene expression of PGC1␣ was increased in response to fatty acids, but the relative response was blunted in diabetic myotubes compared with control cells. In C2C12 myotubes, PGC1␣ expression was enhanced after 4 h but reduced after 16 h of incubation with palmitic acid (35), whereas unsaturated fatty acids like oleic acid and linoleic acid enhanced PGC1␣ expression in human myotubes (36). Our data suggest that the reduced capacity for complete mitochondrial fatty acid oxidation observed for type 2 diabetes myotubes might be related to suboptimal responses in expression of PGC1␣, e.g., when the myotubes are exposed to fatty acids.…”
Section: Discussionmentioning
confidence: 73%
“…Mice with muscle-specific overexpression of lipoprotein lipase, which increases fatty acid influx into skeletal muscle, display extensive mitochondrial proliferation (32). Fatty acids have also been shown to increase PGC-1␣ expression in muscle cells (33) and ␤-cells (34), and this is associated with increased mitochondrial metabolism (33,35). The fatty acid subtype appears to be important (33), as palmitate alone reduces PGC-1␣ expression (36); however, this may be related to its activation of inflammatory pathways that are known to impact on PGC-1␣ expression (37).…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acids have also been shown to increase PGC-1␣ expression in muscle cells (33) and ␤-cells (34), and this is associated with increased mitochondrial metabolism (33,35). The fatty acid subtype appears to be important (33), as palmitate alone reduces PGC-1␣ expression (36); however, this may be related to its activation of inflammatory pathways that are known to impact on PGC-1␣ expression (37). The coordinated increase in the activity of ␤-oxidation and trichloroacetic cycle enzymes, along with the increased expression of respiratory chain subunits observed in the current study, suggest that PGC-1␣ is in part mediating the increase in fatty acid oxidative capacity and mitochondrial content by coactivating its known binding partners estrogen-related receptor ␣, PPAR␣, PPAR␦, and nuclear respiratory factor-1 (15).…”
Section: Discussionmentioning
confidence: 99%
“…Obese, insulin-resistant and type 2 diabetic states reveal low muscle mitochondrial oxidative capacity, reduced expression of respiratory chain components, and decreased expression of the gene encoding PGC-1α (PPARGC1A) [2,3]. We have recently shown that PPARGC1A expression in in vitro differentiated human skeletal muscle cells (myotubes) is induced by common unsaturated plasma NEFAs, such as palmitoleate, oleate and linoleate, but is not influenced by common saturated NEFAs, such as myristate, palmitate and stearate [4]. In the present study, we investigated (1) whether the basal expression of PPARGC1A and the gene encoding its close homologue, PGC-1β (PPARGC1B) in myotubes derived from metabolically characterised white donors display marked individual variations, and, if so, (2) whether these variations are linked to in vivo metabolic features of the donors, such as adiposity, insulin resistance, total NEFA concentration, or concentration of individual plasma NEFAs.…”
mentioning
confidence: 99%
“…Myoblasts were grown from satellite cells obtained from percutaneous needle biopsies performed on the lateral portion of musculus quadriceps femoris and were differentiated into myotubes as described previously [4]. Firstpass cells were used.…”
mentioning
confidence: 99%